ANALYSIS OF THE LEVEL OF VISITOR SATISFACTION WITH INFORMATION MANAGEMENT PROVIDED IN ONLINE APPLICATIONS BY HOTELS - Kasmin; Rohani Lestari Napitupulu; Slamet Pamuji (Adisam Publisher, 2024)
Management Information Systems have an important role in meeting human needs in an organization. Management Information Systems help present information to provide operational, management and decision- making functions. With this web-based (online) hotel management information system, the following conclusions can be drawn: This online system is able to display customer data, employee data, room data and other data clearly because of the availability of a good database in the form of computer files. With this online information system, it makes it easier for customers to find out hotel information and the hotel's room booking system. This new system can make it easier for customers to administer payments at banks that have collaborated with the hotel, so that guests do not have to come directly to the hotel, because there is a good hotel website to visit via the internet. This hotel management information system provides information from the hotel to customers who want to book rooms. So the hotel no longer needs to count the occupied rooms in the guest book.